2006
DOI: 10.4049/jimmunol.177.4.2552
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Recombinant Vaccine Protects against Monkeypox

Abstract: The smallpox vaccine Dryvax, a live vaccinia virus (VACV), protects against smallpox and monkeypox, but is contraindicated in immunocompromised individuals. Because Abs to VACV mediate protection, a live virus vaccine could be substituted by a safe subunit protein-based vaccine able to induce a protective Ab response. We immunized rhesus macaques with plasmid DNA encoding the monkeypox orthologs of the VACV L1R, A27L, A33R, and B5R proteins by the intradermal and i.m. routes, either alone or in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 32 publications
2
137
0
Order By: Relevance
“…However, both DNA [16] and protein [11] immunization studies indicated that multicomponent vaccines eliciting antibodies to MV and EV proteins provided better protection against VACV than single component vaccines. In addition, monkeypox virus (MPXV) DNA priming and protein boosting provided better protection in a MPXV model than either alone [17]. Results obtained by passive administration of polyclonal or monoclonal IgGs to A33, B5 and L1 suggested that antibodies are important for the protection achieved by protein vaccines [18,19].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, both DNA [16] and protein [11] immunization studies indicated that multicomponent vaccines eliciting antibodies to MV and EV proteins provided better protection against VACV than single component vaccines. In addition, monkeypox virus (MPXV) DNA priming and protein boosting provided better protection in a MPXV model than either alone [17]. Results obtained by passive administration of polyclonal or monoclonal IgGs to A33, B5 and L1 suggested that antibodies are important for the protection achieved by protein vaccines [18,19].…”
Section: Introductionmentioning
confidence: 90%
“…A33R, and B5R) administered percutaneously with a gene gun [63]. In a recently published study [17], it was reported that a 4-component DNA vaccine composed of MPXV orthologs of the same VACV genes administered intramuscularly did not induce neutralizing antibody or protect monkeys against a MPXV challenge. In contrast, the corresponding recombinant MPXV proteins with alum or CPG ODNs provided partial protection, which was enhanced by prior DNA vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have shown that vaccines comprised of combinations of immunogens targeting both infectious forms of orthopoxvirus, IMV and EEV, provides superior protection versus targeting only IMV or EEV [19][20][21][22][23][24]41,49,50]. IMV neutralizing antibodies, including those against L1 and A27, neutralize virus in the initial exposure and also can eliminate any IMV released from infected cells that are lysed or EEV that are disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…This dose is three times the LD 50 . Subsequently, mice were observed and weighed daily for 14 d. Moribund mice (>30% body weight) were euthanized.…”
Section: Viral Challengesmentioning
confidence: 99%
See 1 more Smart Citation